"My cheeks get red and my brain gets scared": A computer assisted interview to explore experiences of anxiety in young children on the autism spectrum. (June 2021) - Simpson, Kate; Adams, Dawn; Ambrose, Kathryn; Keen, Deb
Abstract: Background: Anxiety symptoms are common in children on the autism spectrum and may be present at an early age. While a multi-informant approach is considered best practice in the assessment of anxiety, self-reports from young children on the autism spectrum are rarely included. Aims: The aim of this study was to utilise a computer-assisted interview procedure incorporating visual prompts to elicit the viewpoints of children about their experiences of anxiety. Methods and procedures: Ten children aged 5–8 years who were diagnosed on the autism spectrum completed the interview. Directed content analysis was used to explore the data generated in the interview. Outcomes and results: A wide range of situations that trigger anxiety, and responses to anxiety, were reported across the participant group. These responses may be unrecognised as anxiety by others. The children provided positive feedback on the use of the computer-assisted interview. Conclusions and implications: The child's own self-report can inform parents and professionals of the situations which make them more or less anxious and the behaviours that they use to communicate their anxiety in that specific situation. The use of a computer-assisted interview may be an effective method to support self-report of anxiety-related experiences for young children on the autism spectrum.